Analyses of tail length, skin lesions and active behaviour pattern of pigs in the context of genetics, feeding and genotype by feeding interactions - Aikins-Wilson, Sheila; Justus Liebig University Giessen (My University, 2023)
A major unsolved welfare issue in pigs is aggressive and tail biting behaviour. This behaviour is induced by environmental, genetic, and nutritional factors. Genetic components as well as genotype by environment interactions have been identified to affect primary and functional trait responses to biting in pigs. Furthermore, one key trigger for tail biting is the length of the tail. The persistence of tail biting in commercial farm conditions has resulted in the majority of large pig enterprises considering docking of the tails of all piglets as a preventative measure, which does not correspond with legal animal welfare guidelines. Nevertheless, the future is to keep pigs with naturally long tails, implying improvements in animal breeding and behaviour. It remains unclear why some pigs are not victims of this aggressive behaviour in farm houses. Furthermore, it is imperative to identify the exact causes of abnormal behaviour, especially from a genetics perspective. Aggressive behaviour and tail biting in pigs can be mitigated by the use of breeding strategies and the modification of the production environment. This study focuses on the traits tail length, skin lesions and active behaviour pattern of pigs in the context of genetics, feeding and genotype by feeding interactions in pigs. Due to the lack of investigations in the literature addressing genetic parameters for tail characteristics and its effect on growth traits, Chapter 2 is the first comprehensive report on genetic parameters for tail length (T-LEN). The chapter reported on T-LEN and growth traits: birth weight (BW), weaning weight (WW), post-weaning weight (PWW), and average daily gain (ADG) from 9,348 piglets from the University of Gießen research station. In addition, 4,943 binary observations from 1,648 pigs for tail lesions (T-LES) as indicators for tail necrosis, tail abnormalities, or tail biting were included in this analysis. T-LES were recorded at 30 ± 7 days after entry for rearing (T-Les-1), at 50 ± 7 days after entry for rearing (end of the rearing period, T-LES-2), and 130 ± 20 days after entry for rearing (end of fattening period, T-LES-3). Heritability estimate for T-LEN was 0.42 (± 0.03), indicating the potential for genetic selection on short tails. The maternal genetic heritability for T-LEN (0.05 ± 0.04), indicating the influence of uterine characteristics on morphological traits. The negative correlation between direct and maternal effects for T-LEN of – 0.35 (± 0.13), as well as the antagonistic relationships between T-LEN with the growth traits BW, WW, PWW, and ADG, complicate selection strategies and breeding goal definitions. The heritability for T-LES when considering the three repeated measurements was 0.23 (± 0.04) from the linear (repeatability of 0.30) and 0.21 (± 0.06; repeatability of 0.29) from the threshold model. The breeding value correlations between T-LES-3 and breeding values from the repeatability models were quite large (0.74 to 0.90), suggesting tail lesion recording at the end of the rearing period. Nutrition plays a major role in pig behaviour such as the favourable feeding effects of the chicory herbal diet to reduce aggressiveness and simultaneously improve growth performance. For this reason, the aim of Chapter 3 was to assess the feeding effect of the chicory herbal diet on production traits and lesions scores, and to study possible boar-diet and genotype by diet interactions in post weaning pigs. A cross-classified research design was implemented, focussing on an equal number of boar offspring in both feeding groups. Findings in chapter 3 indicate that the dietary treatment had no significant effect (P > 0.05) on growth traits (PWW and ADG). However, the dietary treatment significantly (P < 0.05) influenced the behaviour of the pigs, with a lower and favourable lesion score for the pigs allocated to herbal diet (HD; basal diet plus a supplement with chicory herbs). Results from the study indicate the importance of genotype by feeding interactions for pig breeding, suggesting specific boars for different feeding environments. Chapter 4 provides an insight into the behavioural adaptation of individual piglets in the weaning stage kept in two different dietary environments. The backtest score (BT) behavioural tests was performed on piglets and classified as high-resisting (HR), low-resisting (LR) or intermediate-resisting (IR). Piglets were grouped based on the BT as well as the relative breeding value for skin lesions (RBV-LS) estimated for the sires. Video recordings of individual piglets were obtained and analysed on day one and at five weeks after weaning. Each animal was video monitored for 300 minutes for eight different behaviour traits. The aggressive behaviours traits and general activities decreased five weeks post weaning compared to the first day of weaning. Pigs classified as HR piglets were more aggressive than the LR and IR contemporaries, with significantly higher least squares means (lsmeans) for fight, ear or tail bite and exploration. The level of aggressiveness observed in the two dietary environments suggest that the herbal diet contributed to calm pig behaviour. Backtest scores as well as breeding values from a victim perspective (lesion scores) can be used as indicator traits for selection against aggressiveness. Chapter 5 captured the results from the data and observations used for the analysis from chapters 2, 3 and 4. This chapter focussed on a general discussion based on the results from the previous chapters and presents conclusions drawn from the analyses. Recommendations were also given based on the findings, considering concerns and suggestions. In this regard, the heritability estimate for T-LEN suggested the possibility for breeding pigs with short tails. However, the maternal genetic influence on T-LEN as well as the correlations between T-LEN and traits of economic importance have to be taken into account when defining overall breeding goals. The importance of genotype by feeding interactions was detected, indicating re-rankings of sires in different feeding environments, and the favourable effect of herbal diet on pig behaviour.
Keywords: Genetics studies on pig behaviour; Genetic parameters; Tail length; Tail lesions; Skin lesions; Video behaviour traits; Piglet backtest; Herbal diet; Growth parameters; Growth traits; Maternal effects; Genotype by environment interactions; Breeding value associations; ddc:630